Inhibition of EGFR-STAT3 signaling with erlotinib prevents carcinogenesis in a chemically-induced mouse model of oral squamous cell carcinoma - Leeman-Neill, Rebecca J. (2010)
Chemoprevention of head and neck squamous cell carcinoma (HNSCC), a disease associated with high mortality rates and frequent occurrence of second primary tumor (SPT), is an important clinical goal. The epidermal growth factor receptor (EGFR)-signal transducer and activator of transcription (STAT)-3 signaling pathway is known to play a key role in HNSCC growth, survival and prognosis, thereby serving as a potential therapeutic target in the treatment of HNSCC. In the current study, the 4-nitroquinoline-1-oxide (4-NQO)-induced murine model of oral carcinogenesis was utilized to investigate the chemopreventive activities of compounds that target the EGFR-STAT3 signaling pathway. This model mimics the process of oral carcinogenesis in humans. The drugs under investigation included erlotinib, a small molecule inhibitor of the EGFR, and guggulipid, the extract of an Ayurvedic medicinal plant, which contains guggulsterone, a compound known to inhibit STAT3. Dietary administration of guggulipid failed to confer protection against oral carcinogenesis. On the other hand, the mice placed on erlotinib-supplemented diet exhibited a 69% decrease (p< 0.001) in incidence of preneoplastic and neoplastic lesions compared with mice on the control diet. Immunostaining of dysplastic lesions demonstrated modest decreases in STAT3 levels, with both drug treatments, that were not statistically significant. The results of the present study provide the basis for exploring the efficacy of erlotinib for prevention of HNSCC in a clinical setting.